Kuat Tekan Beton Dengan Substitusi Parsial Pecahan Keramik Pengganti Agregat Kasar Campuran Beton - Oka Darmayasa, I Gede (Jurnal Ecocentrism, 2023)
With the rapid development at this time, the need for building materials continues to increase, especially concrete-forming aggregates. In this study, ceramic shards were used as an ingredient in the concrete mixture and compared with concrete in the same mixture composition. The research was conducted in the laboratory on the constituent materials in the concrete mix, namely cement, sand and crushed stone. To find out whether the alternative material, namely ceramic shards, meets the requirements, a test is carried out, namely through a concrete compressive strength test. The compressive strength test was carried out by making a mixture of normal concrete and concrete mixed with ceramic shards starting at a proportion of 10%, 20%, 30% and 40%. In this study, a cube test object measuring 15 x 15 x 15 cm was used. The mixed concrete mix was prepared in 8 trials for each proportion and the compressive strength test was carried out at 14 days and 28 days of age. The results of the research showed that the ceramic shards fulfill the requirements as aggregates in the concrete mix, according to the compressive strength value of the resulting concrete. namely concrete K225.